Assessment of the antimicrobial activity of essential oils from some Beninese medicinal plants :Influence of different tweens - BABA-MOUSSA, LAMINE SAÏD; DOUGNON, T. VICTORIEN (My University, 2016)
Medicinal plants have an important place in the therapy mechanism of Benin's population. According to the World Health Organization, 75% of African populations use plants for treatment. Many researchers used to work with tweens. Thus, this work aimed to study the influence of the use of different types of tween in the evaluation of the antimicrobial activity of four essential oils. It helped also to determine the minimum inhibitory and bactericidal concentrations of those oils including their chemical compositions. Essential oils from some plants were obtained. The sensitivity of germs namely Micrococcus luteus ; Staphylococcus aureus ATCC 29213 ; Proteus mirabilis ATCC 24974 ; Pseudomonas aeruginosa ATCC 27853 ; Candida albicans IP 4872 to the various essential oils by microdilution technique was tested. Two chromatographic analyzes were performed for each oil on a gas chromatograph electronically controlled pressure. Results and Implications: Tween 60 has the best features, tweens 20 and 40 at 5% do not allow having a good dispersion of the essential oils in liquid media and a good spread in agar media. Furthermore, tween 80 seems to have a synergistic action with the essential oils although it shows good results. The chemical analysis showed several major compounds: myrcene (11.48%), neral (33.53%), geranial (43.10%), estragole (97.10%), limonene (61.40%), 1,8-cineole (61.60%). The minimum inhibitory concentrations (MIC) of the oils range between 0.078 and 10 mg / ml and the Minimum Bactericidal Concentrations (CMB) range from 0.078 to 10 ml /ml.
Keywords: Essential oil; Tween; medicinal plants; antimicrobial activity; mouthwash.